Secondary Caries in situ Models: A Systematic Review - Hollanders, Audrey C.C. (Caries Res, 2018)
In situ caries research serves as a bridge between clinical research and laboratory studies. In this kind of research, volunteers wear a removable intraoral splint or prosthesis containing research samples. Many different in situ models exist to investigate secondary caries. This systematic review compared currently existing secondary caries models and their lesion progression per day values. MATERIALS AND METHODS: Three databases (Medline, Embase, and Cochrane) were searched for relevant literature. Bias risk was assessed and model parameters and caries-related outcomes were extracted by 2 independent researchers. Where possible, caries-related outcomes were normalized by estimating lesion progression per day by dividing lesion depth extracted from microradiographic or microhardness data by the number of days the study lasted. RESULTS: The literature search identified 335 articles. After eliminating duplicates and selection, 31 articles were included. The models differed greatly on factors such as sample location, presence of fluoride in the model, and analysis methods. Three main groups could be identified by sample placement; 68% of models placed samples palatally in the upper jaw, and the lower jaw model could be divided into the buccal (26%) and approximal (6%) areas. Average lesion progression in enamel next to composite was 4.3 ± 2.8 µm (range1.1–8.8 µm/day). DISCUSSION: Studies conducted with palatal models showed caries progression rates 2–5 times higher than the estimated clinical progression rates. Lesion progression per day could be a useful tool for future comparison of models and establishing a standardized model.